2014
DOI: 10.1002/adma.201402328
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Piezo‐phototronic Nano‐LEDs

Abstract: Two-dimensional finite-element simulation of the piezo-phototronic effect in p-n-junction-based devices is carried out for the first time. A charge channel can be induced at the p-n junction interface when strain is applied, given the n-side is a piezoelectric semiconductor and the p-type side is non-piezoelectric semiconductor. This provides the first simulated evidence supporting the previously suggested mechanism responsible for the experimentally observed gigantic change of light-emission efficiency in pie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 19 publications
3
53
0
Order By: Relevance
“…In our previous work, we have demonstrated that piezophototronic effect can be utilized to largely enhance light emitting intensity (to $ 200%) of a single ZnO wire inorganic/ organic hybrid LED [12], and the results are well supported by a theory proposed for piezo-phototronics for studying the photon emission at a p-n junction with the presence of local piezoelectric charges [13][14][15][16][17][18]. However, the piezo-phototronic effect has not been demonstrated in a vertical aligned ZnO wire inorganic/organic hybrid LEDs array, which have greater application than a single lateral NW LED in future.…”
Section: Introductionsupporting
confidence: 56%
“…In our previous work, we have demonstrated that piezophototronic effect can be utilized to largely enhance light emitting intensity (to $ 200%) of a single ZnO wire inorganic/ organic hybrid LED [12], and the results are well supported by a theory proposed for piezo-phototronics for studying the photon emission at a p-n junction with the presence of local piezoelectric charges [13][14][15][16][17][18]. However, the piezo-phototronic effect has not been demonstrated in a vertical aligned ZnO wire inorganic/organic hybrid LEDs array, which have greater application than a single lateral NW LED in future.…”
Section: Introductionsupporting
confidence: 56%
“…Both the conduction and valence band of ZnO at the interface of pn junction increase as a result based on Anderson's model (Figure 1e). [25,28] Therefore, the charge carriers' transport across the heterojunction is significantly enhanced during this process and hence a transient high output current is observed from the measurements (Figure 2a). The temperature variation vanishes rapidly, [22] and the photocurrent gradually stabilizes at some certain value due to the relatively slow photoexcitation process.…”
Section: Communicationmentioning
confidence: 93%
“…The conduction and valence band of ZnO decrease and form a "carrier trap" effect due to positive pyropolarizations as shown in Figure 1f. [25,28] Such "trap" greatly hinders the carriers' transport across the pn junction and the dark current is greatly reduced. Moreover, since the pyroelectric …”
Section: Communicationmentioning
confidence: 99%
“…70 The strain modulation on the p-n junction could be explained through the width change of the depletion zone and the band diagram deformation. 71 Take a light-illuminated p-n junction with an n-type piezoelectric semiconductor as an example. Negative polarization charge will be introduced at the interface in the n-type side (Fig.…”
Section: Effect Of Piezo-charge On the P-n Junctionmentioning
confidence: 99%